Separation from parents during childhood trauma predicts adult attachment security and post-traumatic stress disorder. Issue 11 (24th May 2017) - Bryant, R. A.; Creamer, M.; O'Donnell, M.; Forbes, D.; Felmingham, K. L.; Silove, D.; Malhi, G.; van Hoof, M.; McFarlane, A. C.; Nickerson, A.
Abstract : Background: Prolonged separation from parental support is a risk factor for psychopathology. This study assessed the impact of brief separation from parents during childhood trauma on adult attachment tendencies and post-traumatic stress. Method: Children ( n = 806) exposed to a major Australian bushfire disaster in 1983 and matched controls ( n = 725) were assessed in the aftermath of the fires (mean age 7–8 years) via parent reports of trauma exposure and separation from parents during the fires. Participants ( n = 500) were subsequently assessed 28 years after initial assessment on the Experiences in Close Relationships scale to assess attachment security, and post-traumatic stress disorder (PTSD) was assessed using the PTSD checklist. Results: Being separated from parents was significantly related to having an avoidant attachment style as an adult ( B = −3.69, s.e. = 1.48, β = −0.23, p = 0.013). Avoidant attachment was associated with re-experiencing ( B = 0.03, s.e. = 0.01, β = 0.31, p = 0.045), avoidance ( B = 0.03, s.e. = 0.01, β = 0.30, p = 0.001) and numbing ( B = 0.03, s.e. = 0.01, β = 0.30, p < 0.001) symptoms. Anxious attachment was associated with re-experiencing ( B = 0.03, s.e. = 0.01, β = 0.18, p = 0.001), numbing ( B = 0.03, β = 0.30, s.e. = 0.01, p < 0.001) and arousal ( B = 0.04, s.e. = 0.01, β = 0.43, p < 0.001) symptoms. Conclusions: These findings demonstrate that brief separation from attachments during childhood trauma can have long-lasting effects on one's attachment security, and that this can be associated with adult post-traumatic psychopathology.